“Understanding the Fabric of the Natural World.” The Role of the Collective Protagonist in Annie Proulx’s Barkskins - Leonardo Nolé (Università degli Studi di Torino, 2020)
Contemporary Anthropocene narratives often choose to engage with large scales of space and time. As a consequence, according to Ursula K. Heise, “the single protagonist may decrease in importance, since epic-style narratives over the last century have tended to shift the major narrative actants from individual human characters to collective and sometimes nonhuman actors.” Annie Proulx’s latest novel, Barkskins (2016), is a fitting example of this tendency. Despite its commitment to several human characters, Barkskins never forgets about the story of the forest, which in Proulx’s words is “the character, the underpinning of life.” In this essay, I will explore the role this multifaceted collective protagonist plays in Barkskins’ narrative. First, thanks to the many human characters at the center of the plot, the narrative can geographically and historically map people’s past and present movements across America, Europe, Asia, and Oceania, taking the timber business as an example of the technological and cultural development of capitalism in different parts of the world and its long-term effects. Second, the making of the forest and several indigenous people into central characters enriches and diversifies Proulx’s discussion of the human impact on the natural world. Finally, its twofold perspective on the actions of single human beings as well as the impact of humanity as a whole bring Barkskins to raise the question of individual/collective agency vis-à-vis the present environmental crisis.